2014
DOI: 10.1103/physrevb.90.224424
|View full text |Cite
|
Sign up to set email alerts
|

Probing magnetoelastic effects of ultrathin antiferromagnets via magnetic domain imaging in ferromagnetic-antiferromagnetic bilayers

Abstract: We report an experimental investigation of the magnetoelastic effects of ultrathin antiferromagnets, performed by comparing the characteristic behavior of the induced spin-reorientation transition (SRT) of Co films in two types of epitaxially grown bilayers: face-centered-cubic (fcc)-like Mn/Co (fcc-Mn: a = 3.75Å, c = 3.76Å) and face-centered-tetragonal (fct)-Mn (a = 3.61Å, c = 3.78Å). Magnetic hysteresis loops and magnetic domain images indicate that both fcc-Mn and fct-Mn films can produce a 110 to 100 SRT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In an independent study, Yamada et al repeated the same measurement on a system with Mn on top of Fe(001), but found the domain-wall width to be nearly independent of the Mn thickness [19]. Similar frustrated spin configurations have also been reported in other systems [8,9,[20][21][22][23][24][25][26][27][28][29][30]. The frustration induced domain wall in nanorings is considered to lead to potential logic and memory applications [31].…”
Section: Introductionmentioning
confidence: 71%
“…In an independent study, Yamada et al repeated the same measurement on a system with Mn on top of Fe(001), but found the domain-wall width to be nearly independent of the Mn thickness [19]. Similar frustrated spin configurations have also been reported in other systems [8,9,[20][21][22][23][24][25][26][27][28][29][30]. The frustration induced domain wall in nanorings is considered to lead to potential logic and memory applications [31].…”
Section: Introductionmentioning
confidence: 71%
“…Current approaches to circumvent such issues involve strategies such as alloying or engineering the crystalline structure to increase the T Ordering of AFM films. 13,16,17) An alternative approach to promote the thermal stability of long-range AFM ordering in AFM ultrathin films involves applying magnetic proximity effects, which describe an increase in the T Ordering of one magnetic film from another higher-T Ordering magnetic layer through direct exchange coupling. [18][19][20] By applying such an effect, a study showed that the PMA of Fe/Mn bilayers is enhanced after the incorporation of a perpendicular magnetic ultrathin Fe supporting layer.…”
mentioning
confidence: 99%